PENGARUH PENGETAHUAN TENTANG PERBANKAN SYARIAH TERHADAP MINAT MENABUNG SISWA PADA BANK MINI SYARIAH SMK IT AL-IZHAR PEKANBARU - Nurkholif, Fazil; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: This study aims to determine the influence of knowledge about Islamicbanking on students' interest in saving at the Mini Islamic Bank of SMK IT Al-IzharPekanbaru. The research used a quantitative descriptive method. The populationconsisted of 150 students, and a sample of 38 students was obtained using a samplingtechnique of 25% of the population. Data were collected using a questionnaire with aLikert scale. The data analysis technique used was simple linear regression. The resultsshowed that knowledge of Islamic banking had a significant influence on students'saving interest, as indicated by the t value of 6.222, which is greater than the t tablevalue of 1.660, and a significance level of 0.000 < 0.05. The coefficient of determination(R²) was 0.953, indicating that 95.3% of the variation in students’ saving interest can beexplained by knowledge of Islamic banking.Key Words: Islamic Banking Knowledge, Saving Interest, Mini Islamic Bank